Graphene and polytetrafluoroethylene synergistically improve the tribological properties and adhesion of nylon 66 coatings. (October 2017) - Masood, Muhammad T.; Papadopoulou, Evie L.; Heredia-Guerrero, José A.; Bayer, Ilker S.; Athanassiou, Athanassia; Ceseracciu, Luca
Abstract: In this work, we exploit the bidimensional structure and high stiffness of graphene to improve the tribological response of nylon-based composites. Graphene nanoplatelets, coupled with polytetrafluoroethylene microparticles, synergistically improve the friction coefficient and wear rate, as well as the adhesion to the substrate. The enhancement, as high as threefold for both friction and wear rate at the optimal graphene concentration (0.5% in weight), depends upon the formation of a continuous, robust transfer film with the steel rubbing counterpart, as shown by Raman measurements. The graphene-nylon coating also shows three-fold improved adhesion to the underlying substrate, attributed to the high surface energy of graphene. Graphical abstract: